On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China - Chen, Zhi-Teng (Zootaxa, 2019)
Flavoperla basomarginata sp. nov. is described and illustrated as a new species of the genus Flavoperla Chu, 1929 from Sichuan Province of southwestern China. The new species is characterized by the male having an unpigmented head, a “butterfly-shaped” epiproct sclerite, a boot-shaped hammer in lateral view, and the basolaterally sclerotized paraprocts. Morphology of the new species is compared with similar taxa. A provisional key is provided for known Flavoperla males. Relevant taxonomic information and a distribution map for described Flavoperla species are discussed.